2019
DOI: 10.1088/1361-6641/aaf58f
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication technology for high light-extraction ultraviolet thin-film flip-chip (UV TFFC) LEDs grown on SiC

Abstract: The light output of deep ultraviolet (UV-C) AlGaN light-emitting diodes (LEDs) is limited due to their poor light extraction efficiency (LEE). To improve the LEE of AlGaN LEDs, we developed a fabrication technology to process AlGaN LEDs grown on SiC into thinfilm flip-chip LEDs (TFFC LEDs) with high LEE. This process transfers the AlGaN LED epi onto a new substrate by wafer-to-wafer bonding, and by removing the absorbing SiC substrate with a highly selective SF6 plasma etch that stops at the AlN buffer layer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 122 publications
0
21
0
Order By: Relevance
“…A consistent blueshift in the emission wavelengths was observed with decreasing nanowall widths because of the reduced distribution in tensile strain. The LEDs exhibited excellent current-voltage I-V characteristics, including a turn-on voltage of 7 V and current densities of greater than 170 A/cm 2 at 12 V [405] .…”
Section: Molecular Beam Epitaxymentioning
confidence: 99%
“…A consistent blueshift in the emission wavelengths was observed with decreasing nanowall widths because of the reduced distribution in tensile strain. The LEDs exhibited excellent current-voltage I-V characteristics, including a turn-on voltage of 7 V and current densities of greater than 170 A/cm 2 at 12 V [405] .…”
Section: Molecular Beam Epitaxymentioning
confidence: 99%
“…For DUV-LEDs that emit from the back side, internal reflection from the unpolished SSP sapphire surface reduces the light-extraction efficiency (LEE) significantly, in addition to losses due to low reflectivity on the polished top side of the device. Recently, many techniques have been advanced to increase the LEE such as using a super-lattice hole-spreading layer with an Al reflector 20 ; flip chip DUV-LEDs 21 with a roughened AlN template surface 22 ; highly reflective photonic crystals on a p-AlGaN contact layer on top of the DUV-LED structure 23 ; and highly reflective layers and a patterned sapphire substrate 24 . However, improving the LEE by making a nanophotonic crystal (NPhC) on the unpolished side of the single-side-polished (SSP) sapphire substrate has not been done before (the polished side sapphire substrate is for semiconductor growth and the unpolished side is for creating NPhC, where the UV light transmits to the air).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the internal quantum efficiency (η IQE ) can be boosted from 1% to 60% if the dislocation density is decreased from 1 × 10 10 cm −2 to 5 × 10 8 cm −2 [1]. Recently, higher quality AlN and SiC substrates have been developed and used for the growth of DUV LEDs [12][13][14][15][16]. In contrast to substrate and growth optimization, few studies have focused on the engineering of the active region to reduce the both QCSE and tune the optical polarization of emitted light.…”
Section: Introductionmentioning
confidence: 99%